(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
The recent evolution of total factor productivity (TFP) difference across countries has risen significantly, creating a considerable divergence in income per person as a measurement of living standards. However, Indonesia experienced a declining trend in TFP levels persistently. As a lower middle-income country, Indonesia is ambitious to be a high-income country by design, named Indonesia Vision 2045. This study mainly examines the presence of resource misallocation by channel. Higher revenue productivity (TFPR) dispersion leads to inefficiency of allocating resources and causes productivity loss. Secondly, it also examines the source of resource misallocation by observing the relationship between productivity loss and the proxy of policy distortion variables. Furthermore, this study aims to contribute to the misallocation and growth literature by analyzing firm-level data from 2004, 2005, 2012, and 2013. This study assesses the impact of the commodity boom period that spanned between 2002 and 2012–2013, two pivotal events that significantly altered Indonesia’s economic landscape. The TFPR and output productivity (TFPQ) are the dependent variables using large and medium manufacturing annual surveys from the Indonesian Central Bureau of Statistics (BPS). This study discovers that TFPR varied across firms within industries, indicating resource misallocation. Furthermore, equalizing TFPR across sectors would increase aggregate TFP by 122%–133%. Productivity loss relates significantly to ownership, with the elasticity being 1% higher in state-owned enterprises (SOE), equating to a 57.7% increase in the TFPR dispersion. These findings have an important implication for the government policy aligning with the target above. Indonesia should reform SOE to be more productive and profitable while creating a fair playing field. This study also complements by analyzing other policy distortion factors, namely the firm’s location and investment type.